Sendo como se fosse: as danças dramáticas na ação docente do ator-professor - Maria de Lourdes Macena de Souza (2014)
This thesis presents a study on the way of making Dramatic Dances, in order to verify how these spectacular forms can be best used as an educational practice by the actor teacher. Being as it were, it is a term used by the masters of tradition on the direction that is given to the dancers to represent certain dance characters on focus, where they emphasize that each one needs to represent as faithfully as possiblewhat they want to pretend it is, or it is. The need to expand the knowledge about the possibilities of pedagogical approaches with dramatic dances and use these as subjects and/or activities in courses of teacher formation justified this research. The qualitative research, inductive method, exploratory bibliographic studies, documentary research, field research to record sound and imagery guided the methodological path. The theoretical framework was based on studies on the trails inthe field of cultural traditions, spectacular rites, memory, drama and dramatic, educational and liberating praxis, teaching art with educational practices and interterritorias etnocenólógico focus on spectacle and theatricality in dramatic dances. The work dialogues with specific knowledge of Boi Paz no Mundo in the city of Sobral, Pastoril of D. Maririnhada Lo in Paracuru Beach and Boi Ceará of Master Zé Pio inFortaleza, all municipalities in Ceará (Brazil), and also with other author'sexperiences in the field of traditional knowledge, and it engages with subjects related to the field of teacher education in the arts specifically in theater area.